The Shoshoneans : The People of the Basin-Plateau, Expanded Edition - Dorn, Edward (Book collections on Project MUSE., 2013)
""A path-breaking photo narrative of Dorn and African-American photographer Leroy Lucas's mid-1960s travels through Shoshoni Indian country (Nevada, Idaho, Wyoming, and Utah) to paint a stark tableau of modern Native life"--